(untitled) (Tạp chí Y học Cộng đồng, 2024)
Objective: To describe the clinical characteristics of patients with acne vulgaris treated at Tue Tinh Hospital. Subjects and Methods: A descriptive cross-sectional study was conducted on 50 patients diagnosed with acne vulgaris at Tue Tinh Hospital from June 2022 to June 2023. Results: The proportion of female patients (66%) was higher than male patients (34%). The predominant age group was 18–25 years, accounting for 86%. The duration of disease longer than 2 years was observed in 40% of patients. Moderate acne severity was the most common, reported in 68% of cases. The primary lesions were acne comedones and superficial inflammatory lesions, found in 100% of patients. Dietary factors were associated with disease exacerbation in all cases (100%). Conclusion: Acne vulgaris primarily affects young individuals, with a higher prevalence in females compared to males. The disease is generally of mild to moderate severity. Contributing factors such as hormonal disorders, unhealthy dietary habits, and improper use of cosmetics were identified as significant aggravating factors.